Does similarity equal relationship? An archaeological study of Tsindi, a Dzimbahwe site in North-eastern Zimbabwe - Mukabeta, Kelvin (Department of Archaeology, 2019)
Traditionally, archaeological sites making up the Zimbabwe culture were studied using old Childean understanding to the extent that all sites that are smaller than Great Zimbabwe were viewed as lesser important places under its hegemony. Using African centred frameworks, this study represents an attempt to revisit the archaeological site of Tsindi, a Zimbabwe culture site near Marondera in northeastern Zimbabwe. Methodologically, the re-assessment is based on a survey of published and unpublished literature, museum archival records and collections, as well as field surveys, excavations and artefact studies. The study reached convergence with earlier studies on the observation that drystone walls and pottery from upper levels in the sequence of Tsindi are closely related to that from Great Zimbabwe and related sites. However, there are some localised differences within the walls and pottery that speak to contextual innovation and ultimately variation. Available chronological information shows that Tsindi has an earlier Harare tradition occupation which is overlain by levels with Zimbabwe pottery. Combined together, the similarities and differences that appear on identical material culture suggest that Tsindi and Great Zimbabwe were authored by related people who may have interacted with each other directly or indirectly. Recourse to Shona anthropology and history suggests the presence of autonomous political formations (e.g. chiefdoms and states) generally within more than hundred kilometres of each other. If local histories that connect the Nhowe people of north-eastern Zimbabwe to Tsindi are correct, then the site was the capital of a Nhowe chiefdom. In broad terms this suggests the presence of multiple but independent polities on the landscape. Future research must, however, explore in more detail the nature of the relationships between individual polities such as Tsindi and similar ones such as Mutoko, Tere and among others Harleigh Farm that are associated with different chiefdoms.